Layered Double Hydroxide Catalysts Preparation, Characterization and Applications for Process Development: An Environmentally Green Approach - Ateeq Rahman; Rajasekhar Viswanadha Srirama Pullabhotla (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
The adage of new generation of fine chemicals process is the best process applied in the absence of conventional methods. However, many methods use different reaction parameters, such as basic and acidic catalysts, for example oxidation, reduction, bromination, water splitting, cyanohydrin, ethoxylation, syngas, aldol condensation, Michael addition, asymmetric ring opening of epoxides, epoxidation, Wittig and Heck reaction, asymmetric ester epoxidation of fatty acids, combustion of methane, NOx reduction, biodiesel synthesis, propylene oxide polymerization. Layered Double Hydroxides (LDHs) have received considerable attention due their potential applications in flame retardant and has excellent medicinal property for reducing acidity. These catalysts are characterized using analytical techniques, such as: X-ray diffraction (XRD), Fourier-transform infrared (FT-IR), Raman spectroscopy, Thermogravimetric-Differential Thermal Analyzer (TG-DTA), Scanning electron microscope (SEM), Transmission electron microscopes (TEM), Brunauer-Emmett-Teller (BET) surface area, N2 Adsorption-desorption, Temperature programmed reduction (TPR), X-ray photoelectrons spectroscopy (XPS), which gives its overall picture of its structure, porosity, morphology, thermal stability, reusability, and activity of catalysts. LDHs catalysts have proven to be economic and environmentally friendly. The above discussed applications make these catalysts unique from Green Chemistry point of view since they are reusable, and eco-friendly catalysts. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).